2019
DOI: 10.1111/add.14837
|View full text |Cite
|
Sign up to set email alerts
|

Population‐level predictors of changes in success rates of smoking quit attempts in England: a time series analysis

Abstract: AimsTo quantify associations between the success of smoking quit attempts and factors that have varied throughout 2007-2018 at a population level. Design time series analysis using Autoregressive Integrated Moving Average with Exogeneous Input (ARIMAX) modelling. Setting and Participants Data were aggregated from 54 847 pastyear smokers taking part in the Smoking Toolkit Study which involves monthly repeated cross-sectional household surveys of individuals aged 16+ in England. Measurements The input series wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 54 publications
(86 reference statements)
1
16
0
1
Order By: Relevance
“…The results indicate that NVPs played an important role in reducing smoking prevalence in England in 2012–2019. Other studies have found significant impacts of NVPs on smoking cessation [52,57–63] and initiation [64] in England. Based on a time‐series analysis with a 34.3% quit attempt rate of which 35.2% used e‐cigarettes with a 6% increase in quit success rate and 5.4% increase in overall quit rate, Beard et al .…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that NVPs played an important role in reducing smoking prevalence in England in 2012–2019. Other studies have found significant impacts of NVPs on smoking cessation [52,57–63] and initiation [64] in England. Based on a time‐series analysis with a 34.3% quit attempt rate of which 35.2% used e‐cigarettes with a 6% increase in quit success rate and 5.4% increase in overall quit rate, Beard et al .…”
Section: Discussionmentioning
confidence: 99%
“…supermarket) tobacco point-of-sale display ban introduced in England in April 2012 found evidence for a decline in smoking prevalence [21]. Licencing of nicotine replacement therapy for use in harm reduction, and higher expenditure on tobacco control mass media have been found to be associated with the success of quit attempts [26]. Time series analyses have also shown that cuts on tobacco mass media expenditure have been associated with a reduction in use of smoking cessation support [27,28].…”
Section: Covariatesmentioning
confidence: 99%
“…This is particularly true of participants in the nicotine product arms, as e-cigarettes are readily available in England and are widely used without any structured support as an effective tool to quit smoking. 34,35 Recommendations for research…”
Section: Generalisabilitymentioning
confidence: 99%